Developing a health-promoting school using knowledge to action framework - Yogesh Kumar Jain; Nitin Kumar Joshi; Pankaj Bhardwaj; Kuldeep Singh; Praveen Suthar; Vibha Joshi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: There is a lack of organized effort in the arena of school health promotion, which has been recognized as an effective approach to combat the growing incidence of communicable and noncommunicable diseases. With this view, a study was conducted to develop comprehensive and replicable model for health promotion in schools. MATERIALS AND METHODS: The Knowledge to Action (KTA) framework recognized by the World Health Organization as an implementational framework was used in an implementation study in a school of urban Jodhpur to assess the challenges and gaps associated with health promotion interventions in the school. Baseline regarding knowledge application and practices was gathered using interviews with school staff, parents, and group interaction with students. Knowledge synthesis was done by a thorough search of available literature and the gathered baseline. Resource mapping was carried out using checklists developed from knowledge synthesis. Tailor-made tools were constructed for knowledge implementation for each component of the action cycle. Knowledge of facts related to health behaviors among students was evaluated using pre- and postquestionnaires and practical application of knowledge was assessed using a checklist of 28 indicators on a 5-point Likert scale. Values of tests were gathered and compared with test values 3 and 6 months after the implementation of tailored interventions using descriptive and inferential statistics. RESULTS: Increase in correct answers by students (42% to 96%) and average response for indicators on the Likert scale (3.23-4.86) was seen on repeated interventions over 6 months. Tobacco consumption by school staff reduced by 20% and an increase in willingness among teachers was observed on follow-up interviews. CONCLUSION: The study thus developed a model for health promotion in a school with the help of the KTA framework using tailored interventions that could further be evolved in other setups based on local needs and available resources.